Det hänger i luften. Aerial Architecture and Suspended Identities in Jonas Karlsson’s Short Stories - Za, Giovanni (Folia Scandinavica Posnaniensia, 2025)
In Jonas Karlsson’s work the configuration of external or internal, imaginary, concrete or metaphorical spaces is central. The depiction of unstable, aeriform architectures is the primary focus of the short novel Utgången (2012). In this text, the theatre suspended in mid-air serves as a metaphor for the state of suspension experienced by the protagonist and mirrors the opaque identity of the first-person narrator’s dim self. Unstable subjectivities recur throughout the author’s short novels and epitomises the frequently comedic homo karlssonianus. Elsewhere, characterisations of space are equally significant, as seen in the diptych Min kompis på Gondolen, where the building’s suspension reflects the elusiveness of the self and its ethereal identity, and in the short novel Rummet, where the interior of a public office changes its coordinates and physical dimensions. This article investigates spaces in Jonas Karlsson’s literary production within the methodological framework of Geocriticism and in the attempt to highlight connections between the suspended architecture of a location and an elusive subjectivity. What is gained is a novel interpretation of place as thirdspace, hanging afloat the chaosmos, here intended as “the interlocking relationship or space of rhythm and chaos”.